MISREPRESENTATION DALAM KONTRAK : ANALISIS TERJADINYA PERBEDAAN INFORMASI PADA FASE PRA KONTRAKTUAL DENGAN KONTRAK - Indra Sakti; Bismar Nasution; Sunarmi Sunarmi; Suhaidi Suhaidi (USU LAW JOURNAL, 2017)
ABSTRACT In misrepresentation, the provisions that manages the boundaries between the presentation of misleading information and fraud with trickery are still very vague. Fraud according to the prevailing laws is deliberately giving false and incorrect information to persuade the opposing parties to approve. An exposure to a substance in the pre-contractual phase due to any misunderstandings in a contract is called a representation. Then, the legal consequences will be issued in the post-contractual phase. From the background, several problems can be formulated i.e. how misrepresentation occurs in a contract at a pre-contractual phase, how the settlement of disputes is made, how legal protections for the parties who have misrepresented a contract are. In order to analyze the problems above, the normative juridical research which refers to the legal norms related with the publication of an agreement at pre-contractual phase that contains misrepresentation is used. Based on the results of research, it was found out that the misrepresentation was caused by the inconsistency between what was presented by the offeror in the pre-contractual phase and what was done and supposed to be received by the offeree in the post-contractual phase, and it should also be notified that what distinguished misrepresentation from fraud was that whether or not there were the elements of persuasion and trickery in the pre-contractual phase and standard contractual. The ways to settle the misrepresentation was that  by making the  adjustments of the will and was agreed by the parties. Therefore, a pre-contractual document has had the power to be carried out and has the binding power that provides the rights and obligations to be obeyed by all parties.  It reflects the good intention to seek a solution to a misrepresentation. The forms of the legal protections for those who experienced misrepresentation as permanently stipulated in Article 1321 and Article 1365 of the Civil Code without ignoring any forms of the provisions stipulated by not ignoring the repressive and preventive legal protections. The parties of the contract are expected to be more careful to understand the traditions and prevailing legal provisions in the Common Law and Civil Law System. In making a contract, it is suggested that the parties engage with a legal advisor and legal drafter since the pre- contractual phase. Appropriately, the principles of caveat vendor and the principle of caveat emptor, be applied. Particularly, there are not any regulations and statutory provisions that regulate this subject yet. Keywords: Misrepresentation, Pre-contractual and Legal Protection